FAKTOR PENENTU INTENSI BERPERILAKU TIDAK MEROKOK PADA REMAJA PUTRA DI SMA NEGERI 1 TUBAN TAHUN 2015 - Wemmy Noor Fauzia (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2015)
The majority of smoking behavior began in adolescence. According to the data from WHO (2008), 33,3% of the 1,3 billion smoker in the world came from the global population aged 15 years and older. Data from Riskesdas 2013 also showed that in Indonesia, the highest population of the fi rst time smoking in the age group 15–19 years. When someone started to smoke, there must be an underlying intention, which is often infl uenced by various factors. The purpose of this study was to know the factors that influence of no smoking intention in young men, by used subjective norm and perceived behavioral control. This study was quantitative research with proportioned stratifi ed random sampling method of sampling. Selected samples were 68 young men that scattered in X and XI class of SMA Negeri 1 Tuban. The results showed that subjective norm (p = 0,002) and perceived behavioral control (p = 0,047) had a significant effect of the not smoke intention. Subjective norm owned by the young men, showed a tendency not to smoke intention 56,84 times greater than the intention to smoke. If young men had a better control on his behavior, the tendency not to smoke intention 15,06 times greater than the intention to smoke. It can be concluded that the intention of young men in SMA Negeri 1 Tuban not to smoke is infl uenced by subjective norm and perceived behavioral control.Keywords: no smoking intention, perceived behavioral control, subjective norm